Decomposition pathway of KAlH4 altered by the addition of Al2S3 - Sheppard, Drew; Jepsen, L.H.; Rowles, Matthew; Paskevicius, Mark; Jensen, T.R.; Buckley, Craig (ROYAL SOC CHEMISTRY, 2019)
Altering the decomposition pathway of potassium alanate, KAlH 4 , with aluminium sulfide, Al 2 S 3 , presents a new opportunity to release all of the hydrogen, increase the volumetric hydrogen capacity and avoid complications associated with the formation of KH and molten K. Decomposition of 6KAlH 4 -Al 2 S 3 during heating under dynamic vacuum began at 185 °C, 65 °C lower than for pure KAlH 4 , and released 71% of the theoretical hydrogen content below 300 °C via several unknown compounds. The major hydrogen release event, centred at 276 °C, was associated with two new compounds indexed with monoclinic (a = 10.505, b = 7.492, c = 11.772 Å, β = 122.88°) and hexagonal (a = 10.079, c = 7.429 Å) unit cells, respectively. Unlike the 6NaAlH 4 -Al 2 S 3 system, the 6KAlH 4 -Al 2 S 3 system did not have M 3 AlH 6 (M = alkali metal) as one of the intermediate decomposition products nor were the final products M 2 S and Al observed. Decomposition performed under hydrogen pressure initially followed a similar reaction pathway to that observed during heating under vacuum but resulted in partial melting of the sample between 300 and 350 °C. The measured enthalpy of hydrogen absorption (ΔH abs ) was in the range -44.5 to -51.1 kJ mol -1 H 2 , which is favourable for moderate temperature hydrogen applications. Although, the hydrogen capacity decreases during consecutive H 2 release and uptake cycles, the presence of excess amounts of aluminium allow for further optimisation of hydrogen storage properties.